SISTEM INFORMASI PENGELOLAAN DATA ASET PADA KANTOR SEKRETARIAT DAERAH KABUPATEN TEBO: Information Systems, Web, HTML, and MySQL - Megawaty, Merti; Puad, Lailyn; Matin, Abdul (LP2M Universitas Nurdin Hamzah, 2023)
Assets are sources owned by the agency, namely in the form of movable goods, consumables, and disposable goods, asset data management at the Tebo Regency Regional Secretariat Office which still uses the archiving data collection system in the agenda book as a result the agenda book is torn, and data items are difficult to find so that the resulting data is ineffective and causes archives to accumulate in filing cabinets. The formulation of the problem in this thesis research is how to build a Web-based asset data management information system at the Tebo Regency Regional Secretariat Office.